(untitled) (Open Academia: Journal of Scholarly Research, 2023)
When assessing the degree of adaptation of cow Yelin to modern milking equipment in livestock herds, it will be of particular importance to assess the morphological and functional characteristics of the Yelin, depending on the dairy productivity of cows.